Pengaruh Dimensi Kualitas Pelayanan Terhadap Loyalitas Pelanggan Di Wash Up Laundry Palangka Raya (Jurnal Manajemen Sains dan Organisasi, 2021)
Purpose - This study aims to determine the effect of Service Quality Dimensions consisting of Tangibles, Reliability, Responsiveness, Assurance and Emphaty on Customer Loyalty in Wash Up Laundry Palangka Raya. Design/Methodology/Approach - The research method uses an explanatory approach with survey techniques, the number of samples in this study is 60 respondents, while the data analysis technique in this study was to use descriptive analysis techniques and multiple linear analysis techniques. Findings - The results showed that the Service Quality Dimensions consisting of Tangibles, Reliability, Responsiveness, Assurance and Emphaty had a significant effect on Customer Loyalty in Wash Up Laundry Palangka Raya. And the results of the descriptive analysis state that the respondents agree with the indicators proposed.